a-Amidoaldehydes as substrates in rhodium-catalyzed intermolecular alkyne hydroacylation: The synthesis of a-amidoketones - Pal, R; O'Brien, SC; Willis, MC (Wiley, 2020)
We show that readily available α‐amidoaldehydes are effective substrates for intermolecular Rh‐catalyzed alkyne hydroacylation reactions. The catalyst [Rh(dppe)(C6H5F)][BArF4] provides good reactivity, and allows a broad range of aldehydes and alkynes to be used as substrates, delivering α‐amidoketone products. High yields and high levels of regioselectivity are achieved. The use of α‐amidoaldehydes as substrates establishes that 1,4‐dicarbonyl motifs can be used as controlling groups in Rh‐catalyzed hydroacylation reactions.